Quality of life among breast cancer patients at Kuala Lumpur General Hospital, Malaysia - Ganesh, Sri; Lye, Munn Sann; Lau, Fen Nee (Asian Pacific Organization for Cancer Prevention, 2015)
Background: Among the factors reported to determine the quality of life of breast cancer patients are socio- demographic background, clinical stage, type of treatment received, and the duration since diagnosis.